ผลของโปรแกรมการบำบัดทางความคิดและพฤติกรรมต่ออาการทางลบของผู้ป่วยจิตเภทในชุมชน - ขุมทรัพย์ ก้อนทอง (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The purpose of this quasi-experimental pretest-posttest with control group research design was to examine the effect of cognitive behavioral therapy program on negative symptoms of schizophrenic patients in community. Subjects were 40 schizophrenic patients, aged 20-59 years, at the out-patient department in a psychiatric hospital, Ministry of Public Health. They were matched pair with sex and adequacy of income then randomly assigned to the experimental and control groups, 20 subjects in each group. The experimental group received cognitive behavioral therapy. The control group received regular nursing care. Research instruments consisted of the cognitive behavioral therapy program, the negative syndrome scale and the automatic negative thought. All instruments were certified for content validity by 5 professional experts. Reliability of the negative symptom test and automatic negative thought test were reported by Chronbach’ Alpha Coeffcient 0.5 of .82 and .88, respectively. Data were analyzed by descriptive statistics, dependent and independent t-tests. Findings were as follows: 1. The negative symptoms of schizophrenic patients in community afterreceiving the CBT program was significantly lower than that before (p < .05). 2. The negative symptoms of schizophrenic patients in community after receivedCBT program was significantly lower than that of those who receiving regular nursing care (p < .05). The results suggest that the CBT program is effective in reducing negative symptoms of schizophrenic patients. The program promotes patients’ new skill to identify negative thoughts, form adaptive thoughts, and adjust to particular situations.